Actualization of Indonesian cultural values towards digital film - M.Ruhly Kesuma Dinata; Nikmah Rosidah; Muhammad Fakih; Rudi Natamiharja (Trigin Publisher, 2023)
The emergence of digital film platforms such as VIU and Netflix Disney + Hostar, WeTV, and so on, which makes watching movies easy, you don't have to go to the cinema, you just need a smart phone and the internet to watch movies anywhere. However, in the digital Film Platform Film. Even though the Film Censorship Institute (LSF) has the task of deciding which parts of a film are acceptable for viewing or must be cut or removed, as well as issuing Film Censorship Certificates for use in Indonesian media. What is the history of the development of film law in Indonesia? And how is the actualization of Indonesian film law in the era of globalization? The normative juridical research method is library law research which is carried out by examining library materials or secondary data. State responsibility in protecting Pancasila values ​​from the impact of filmdigital released by digital film platforms that are inconsistent with national values, there is no institution authorized to censor filmsdigital even though the Indonesian state has a Film Censorship Institution (LSF). that there is a legal vacuum to maintain cultural values ​​or to achieve the objectives of the film law in an era that knows no territorial boundaries.